Phytochemical, and Antioxidant Properties of Terminalia chebula Fruit from the Coal-mining environment of Bokaro District, Jharkhand (International Journal of Food and Nutritional Sciences, 2022)
This study investigates the ethnobotanical significance, phytochemical composition, and antioxidant potential of the aqueous extract of Terminalia chebula fruit, collected from the coal-affected forests of Bokaro District, Jharkhand